Reversible ionic liquid-based binder, slurry composition, electrolyte layer and lithium battery

By using reversible ionic liquid-based binder and slurry composition, an ultra-thin oxide electrolyte layer was prepared, and the problems of low energy density and poor interface contact caused by the thickness and rigidity of oxide ceramic electrolytes in all-solid lithium batteries were solved, thus achieving the problem of low energy density and poor interface contact caused by the thickness and rigidity of oxide ceramic electrolytes in all-solid lithium batteries. High energy density and high safety battery performance.

CN119432271APending Publication Date: 2025-02-14DONGFENG MOTOR GRP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411329793.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Due to the thickness and rigidity of the oxide ceramic solid electrolyte, existing all-solid state lithium batteries have low energy density and poor interface contact, making it difficult to achieve high energy density and high safety batteries.

Method used

Using reversible ionic liquid-based binder and slurry composition, an ultra-thin oxide electrolyte layer is formed by mixing ionic liquid, acrylamide monomer and crosslinking agent, and the electrolyte layer is improved by heating, baking and photocuring. Thinness and bondability.

Benefits of technology

The preparation of ultra-thin oxide electrolyte layer is realized, with a thickness of ≤20μm, an ionic conductivity of ≥0.45mS/cm, and a peel strength of ≥3.5N/m, which improves the energy density and interface contact of the battery, enhances the safety of the battery and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432271A_ABST
    Figure CN119432271A_ABST
Patent Text Reader

Abstract

The invention provides a reversible ionic liquid-based binder, a slurry composition, an electrolyte layer and a lithium battery, and belongs to the field of lithium batteries. The binder is used for a solid electrolyte of a lithium battery, and comprises the following components: an ionic liquid, an acrylamide monomer and a cross-linking agent, and the mass ratio of the ionic liquid to the acrylamide monomer to the cross-linking agent is (5-9): (0.5-2.5): (0.5-2.5). By reasonably designing the components and content of the reversible ionic liquid-based binder, a monomer and a cross-linking agent form a cross-linked polymer with a three-dimensional network structure, and meanwhile, the ionic liquid is used as a main body for adjusting polymerization, and the monomer and the cross-linking agent jointly form ionic liquid gel as an effective component of the binder; two different requirements of effective demolding of an electrolyte membrane of a lithium battery and tight combination between the electrolyte membrane and an electrode can be met by utilizing the cohesiveness difference of the reversible binder under different conditions, so that the combination between interfaces is improved while an oxide solid electrolyte layer which is thin enough is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a reversible ionic liquid-based binder, a slurry composition, an electrolyte layer and a lithium battery. Background Art

[0002] Traditional liquid lithium-ion batteries contain a large amount of electrolyte, which can easily cause safety hazards. Once a short circuit, overcharge thermal runaway or electrolyte leakage occurs inside the battery, it may cause safety accidents such as battery fire. Since all-solid-state lithium-ion batteries use solid electrolytes instead of traditional liquid electrolytes, they are expected to further improve the capacity, power and life of batteries while solving the safety problems of lithium-ion batteries, which is in line with the future development direction of high-safety and high-energy-density lithium-ion batteries. At present, all-solid-state lithium batteries using high-specific-capacity lithium metal negative electrode materials and oxide ceramic solid electrolytes are widely regarded as the next generation of batteries that can meet demand. Ceramic electrolytes can withstand high temperatures above 1000°C, so batteries using ceramic electrolytes can effectively avoid the risk of fire and explosion.

[0003] However, the density of oxide ceramic solid electrolytes is much higher than that of traditional liquid electrolytes and polymer separators, and the preparation method is mostly cold pressing and sintering, and the thickness is generally greater than 200μm, which will seriously offset the energy density advantage brought by the high specific capacity lithium metal negative electrode. At the same time, because the oxide is very hard, solid-state batteries have rigid interface contact problems. Under simple room temperature cold pressing conditions, the porosity of the battery is very high, which may cause the battery to fail to work properly. Therefore, to achieve higher energy density oxide-based all-solid-state batteries, the electrolyte intermediate layer needs to be made very thin, which not only improves the energy density of the battery, but also reduces the ionic conductivity requirements of the solid electrolyte layer. In response to the above problems, a new oxide electrolyte preparation process is provided to prepare a sufficiently thin oxide solid electrolyte layer while improving the bonding between interfaces. Summary of the invention

[0004] The present application provides a reversible ionic liquid-based binder, a slurry composition, an electrolyte layer and a lithium battery to solve the following technical problem: how to prepare a sufficiently thin oxide solid electrolyte layer while improving the bonding between interfaces.

[0005] In a first aspect, the present application provides a reversible ionic liquid-based binder, which is used as a solid electrolyte for lithium batteries. The components of the binder include: ionic liquid, acrylamide monomer and a cross-linking agent, and the mass ratio of the ionic liquid, acrylamide monomer and cross-linking agent is (5-9):(0.5-2.5):(0.5-2.5).

[0006] Optionally, the ionic liquid is an imidazole ionic liquid, the acrylamide monomer is N,N-dimethylacrylamide, the cross-linking agent is polyethylene glycol diacrylate, and the mass ratio of the imidazole ionic liquid, the N,N-dimethylacrylamide and the polyethylene glycol diacrylate is (6-8):(1-2):(1-2).

[0007] Optionally, the cation of the imidazole ionic liquid includes one or more of 1-alkylimidazole, 1-alkyl-3-methylimidazole and 1-alkyl-2,3-dimethylimidazole, and the anion of the imidazole ionic liquid includes one or more of chlorine, bromine, iodine, tetrafluoroboric acid, hexafluorophosphoric acid, acetic acid, bis(trifluoromethanesulfonyl)imide, nitric acid, peramic acid, hydrogen sulfate, dihydrogen phosphate, trifluoromethanesulfonic acid, trifluoroacetic acid and p-toluenesulfonic acid.

[0008] In a second aspect, the present application provides a slurry composition, which is used for a solid electrolyte of a lithium battery, and the slurry composition comprises: a binder as described in any one embodiment of the first aspect, an oxide electrolyte powder and a dispersant.

[0009] Optionally, in terms of mass fraction, the content of the binder is 50% to 80%, the content of the oxide electrolyte powder is 20% to 50%, and the content of the dispersant is 0.05% to 5%.

[0010] Optionally, the oxide electrolyte powder includes: one or more of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate and lithium lanthanum titanate, and the particle size of the oxide electrolyte powder is 0.1μm to 0.3μm; the dispersant includes one or more of polyvinyl alcohol and polyvinyl acetal.

[0011] In the third aspect, the present application provides an ultra-thin oxide electrolyte layer, which is formed by curing the slurry composition described in any one embodiment of the second aspect, and the electrolyte layer satisfies at least one of the following properties: thickness ≤ 20 μm, ionic conductivity ≥ 0.45 mS / cm, and peel strength ≥ 3.5 N / m.

[0012] In a fourth aspect, the present application provides a method for preparing the ultra-thin oxide electrolyte layer according to the embodiment of the third aspect, the method comprising:

[0013] The ionic liquid, acrylamide monomer and cross-linking agent are mixed and heated to melt to obtain a binder;

[0014] The binder, the oxide electrolyte powder and the dispersant are mixed to obtain a slurry composition;

[0015] The slurry composition is coated on the surface of a hard substrate, and then heated, baked and photocured to obtain a substrate with an ultra-thin oxide electrolyte layer.

[0016] Optionally, the heating and baking temperature is 80° C. to 100° C., and the light curing uses 365nm ultraviolet rays.

[0017] In a fifth aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the ultra-thin oxide electrolyte layer described in the embodiment of the third aspect.

[0018] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0019] The present application provides a reversible ionic liquid-based binder, which is used for solid electrolytes of lithium batteries. The components of the binder include: ionic liquid, acrylamide monomer and crosslinking agent, and the mass ratio of the ionic liquid, acrylamide monomer and crosslinking agent is (5-9): (0.5-2.5): (0.5-2.5). By rationally designing the components and content of the reversible ionic liquid-based binder, the monomer and the crosslinking agent form a crosslinked polymer with a three-dimensional network structure, and the ionic liquid serves as the main body for regulating polymerization, and the two together form an ionic liquid gel as an effective component of the binder. When the prepared ionic liquid gel is cooled below the phase transition temperature, the binder will form a thin and hard layer of ionic crystals between the gel / substrate, thereby giving it higher adhesion; at a phase transition temperature higher than the ionic liquid, the ionic liquid gel gradually becomes soft and elastic, and the adhesion force decreases and disappears, so it can show excellent adhesion reversibility. The difference in adhesion of the reversible binder under different conditions can be used to achieve two different requirements of effective demolding of the electrolyte membrane of the lithium battery and tight bonding with the electrode, so that a sufficiently thin oxide solid electrolyte layer can be prepared. In addition, the prepared electrolyte layer has ultra-high strength and certain adhesion at room temperature, which can improve the problem of poor contact between solid electrolyte interfaces. Thus, the bonding between interfaces can be improved while preparing a sufficiently thin oxide solid electrolyte layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0022] Figure 1 A schematic diagram of a process for producing an ultra-thin oxide electrolyte layer provided in an embodiment of the present application. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0024] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0025] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.

[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0027] The present application provides a reversible ionic liquid-based binder, which is used for a solid electrolyte of a lithium battery. The components of the binder include: an ionic liquid, an acrylamide monomer and a cross-linking agent. The mass ratio of the ionic liquid, the acrylamide monomer and the cross-linking agent is (5-9):(0.5-2.5):(0.5-2.5).

[0028] It should be noted that ionic liquids are liquids composed entirely of ions, wherein room temperature ionic liquids refer to salts that are liquid at or near room temperature and are completely composed of anions and cations. Crosslinking agents are chemical substances that can promote the formation of covalent bonds or other strong interactions between polymer chains, thereby giving polymer materials a three-dimensional network structure. In the preparation and modification of polymer materials, crosslinking agents play a vital role. In this application, the double bonds in the crosslinking agent molecules react with the double bonds in acrylamide monomers or prepolymers to form covalent bonds. As the reaction proceeds, more and more polymer chains are connected to form a crosslinked polymer with a three-dimensional network structure.

[0029] In the embodiment of the present application, the components and contents of the reversible ionic liquid-based binder are reasonably designed, the monomer and the cross-linking agent form a cross-linked polymer with a three-dimensional network structure, and the ionic liquid is used as the main body to regulate the polymerization, and the two together form an ionic liquid gel, thereby retaining the original properties of the ionic liquid, and solving the problem of ionic liquid overflow in the form of a gel, and giving the material higher plasticity, environmental responsiveness and network structure. In addition, when the prepared ionic liquid gel is cooled below the phase transition temperature, the adhesive will form a thin and hard ionic crystal between the gel / substrate, thereby giving it higher adhesion; at a phase transition temperature higher than the ionic liquid, the ionic liquid gel gradually becomes soft elastic, the adhesion force decreases and disappears, and thus can show excellent adhesion reversibility. Thus, the difference in adhesion of the reversible binder under different conditions can be used to achieve two different requirements of effective demoulding of the ultra-thin oxide electrolyte membrane and close bonding with the electrode, and the prepared electrolyte layer has a certain adhesion at room temperature while having ultra-high strength, which can improve the problem of poor contact at the solid electrolyte interface, and provide an effective strategy for constructing an ultra-thin and strong oxide electrolyte membrane with adhesion. The mass ratio of the ionic liquid, the acrylamide monomer and the cross-linking agent is ionic liquid: acrylamide monomer: cross-linking agent = (5-9): (0.5-2.5): (0.5-2.5). Exemplarily, the mass ratio of the ionic liquid, the acrylamide monomer and the cross-linking agent can be 5:2:2, 6:2:2, 7:2:2, 8:2:2, 9:2:2, 7:2:0.5, 7:2:1, 7:2:1.5, 7:2:2.5, 7:0.5:2, 7:1:2, 7:2.5:2, etc.

[0030] In some embodiments, the ionic liquid is an imidazole ionic liquid, the acrylamide monomer is N,N-dimethylacrylamide, the cross-linking agent is polyethylene glycol diacrylate, and the mass ratio of the imidazole ionic liquid, the N,N-dimethylacrylamide and the polyethylene glycol diacrylate is (6-8):(1-2):(1-2).

[0031] In some embodiments, the cation of the imidazole ionic liquid includes one or more of 1-alkylimidazole, 1-alkyl-3-methylimidazole and 1-alkyl-2,3-dimethylimidazole, and the anion of the imidazole ionic liquid includes one or more of chlorine, bromine, iodine, tetrafluoroboric acid, hexafluorophosphoric acid, acetic acid, bistrifluoromethanesulfonyl imide, nitric acid, peramic acid, hydrogen sulfate, dihydrogen phosphate, trifluoromethanesulfonic acid, trifluoroacetic acid and p-toluenesulfonic acid.

[0032] The alkyl group includes one or more of methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, dodecyl, tetradecyl, hexadecyl and octadecyl.

[0033] Based on a general inventive concept, the present application provides a slurry composition, which is used for a solid electrolyte of a lithium battery. The slurry composition includes: a binder, an oxide electrolyte powder and a dispersant as described in any one of the above embodiments.

[0034] In some embodiments, the content of the binder is 50% to 80% by mass, the content of the oxide electrolyte powder is 20% to 50% by mass, and the content of the dispersant is 0.05% to 5% by mass.

[0035] Binder plays a key role in solid electrolyte materials. It can firmly bind oxide electrolyte powders together to form a stable solid structure. It also helps to improve the mechanical strength and durability of the material. At the same time, the present application adopts a reversible ionic liquid-based binder to achieve two different requirements: effective demolding of ultra-thin oxide electrolyte membranes and tight bonding with electrodes. Oxide electrolyte powder is a core component of solid electrolyte materials. It provides a path for ion conduction, allowing the electrolyte to conduct ions in the solid state. The performance of oxide electrolyte powder directly affects the conductivity and other electrochemical properties of the entire material. Dispersants play an auxiliary role in the preparation process of solid electrolyte materials. They help to improve the dispersibility of oxide electrolyte powders in binders, reduce agglomeration, and thus improve the uniformity and performance of materials. The present application rationally designs a slurry composition for solid electrolytes of lithium batteries, so that an ultra-thin oxide electrolyte layer can be prepared while improving the energy density of the battery and reducing the ionic conductivity requirements of the solid electrolyte layer. Exemplarily, the content of the binder can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc., the content of the oxide electrolyte powder can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc., and the content of the dispersant can be 0.05%, 1%, 2%, 3%, 4%, 5%, etc.

[0036] In some embodiments, the oxide electrolyte powder includes: one or more of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate and lithium lanthanum titanate, and the particle size of the oxide electrolyte powder is 0.1μm to 0.3μm; the dispersant includes one or more of polyvinyl alcohol and polyvinyl alcohol acetal.

[0037] Based on a general inventive concept, the present application provides an ultra-thin oxide electrolyte layer, which is formed by curing the slurry composition described in any one of the above embodiments, and the electrolyte layer satisfies at least one of the following properties: thickness ≤ 20 μm, ionic conductivity ≥ 0.45 mS / cm, and peel strength ≥ 3.5 N / m.

[0038] This application can prepare an ultra-thin oxide electrolyte layer through a simple preparation process, improve the energy density of the battery, and reduce the ionic conductivity requirements of the solid electrolyte layer. By utilizing the difference in adhesion of the reversible binder under different conditions, two different requirements of effective demoulding of the ultra-thin oxide electrolyte membrane and tight bonding with the electrode are achieved. The prepared electrolyte layer has a certain degree of adhesion at room temperature while having ultra-high strength, which can improve the problem of poor contact at the solid electrolyte interface, and provides an effective strategy for constructing an ultra-thin and strong oxide electrolyte membrane with adhesion.

[0039] Figure 1 A schematic diagram of a process for producing an ultra-thin oxide electrolyte layer provided in an embodiment of the present application.

[0040] See also Figure 1 Based on a general inventive concept, the present application provides a method for preparing the ultra-thin oxide electrolyte layer described in the above embodiment, the method comprising:

[0041] S1, mixing the ionic liquid, acrylamide monomer and cross-linking agent and heating and melting them to obtain a binder;

[0042] S2, mixing the binder, oxide electrolyte powder and dispersant to obtain a slurry composition;

[0043] S3, coating the slurry composition on the surface of a hard substrate, and then performing heating, baking and photocuring to obtain a substrate with an ultra-thin oxide electrolyte layer.

[0044] In some embodiments, the heating and baking temperature is 80° C. to 100° C., and the photocuring uses 365 nm ultraviolet rays.

[0045] After coating is completed, the substrate is placed in an oven or on a hot plate for heating and baking. The purpose of heating and baking is to remove the solvent in the slurry and promote the curing of the binder, while forming a preliminary connection between the oxide electrolyte powders. The baking temperature is limited to 80°C to 100°C, which can ensure the full volatilization of the solvent without causing excessive thermal decomposition or deformation of the material. At the same time, the baking time is determined according to the composition and thickness of the specific slurry. After heating and baking, photocuring is performed. Photocuring uses ultraviolet rays with a wavelength of 365nm to irradiate the surface of the substrate. Ultraviolet rays can induce chemical reactions in the photosensitive groups in the binder to form a more stable three-dimensional network structure, thereby further strengthening the bonding force between the electrolyte layer and the substrate, and improving the density and conductivity of the electrolyte layer. Exemplarily, the temperature of heating and baking can be 80°C, 85°C, 90°C, 95°C, 100°C, etc.

[0046] The product prepared by the method for preparing an ultrathin oxide electrolyte layer is the above-mentioned ultrathin oxide electrolyte layer. The chemical composition and organizational structure of the ultrathin oxide electrolyte layer prepared by the method for preparing an ultrathin oxide electrolyte layer can refer to the above-mentioned embodiment. Since the method for preparing an ultrathin oxide electrolyte layer adopts part or all of the technical solutions of the ultrathin oxide electrolyte layer embodiment, it has at least all the beneficial effects brought by the technical solutions of the ultrathin oxide electrolyte layer embodiment, which will not be described one by one here.

[0047] Based on a general inventive concept, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the ultra-thin oxide electrolyte layer described in the above embodiment.

[0048] The specific preparation method of the lithium-ion battery includes: heating the oxide electrolyte layer in the above embodiment again and demolding it from the substrate, the heating temperature is the same as the original baking temperature, at this time, an oxide electrolyte layer with a thickness of less than 20 μm can be obtained, which can be directly placed between the positive and negative for stacking assembly, or can be independently packaged into sheets, the oxide electrolyte layer is placed between the positive and negative or the positive / negative electrode sheet coated with the oxide electrolyte layer is assembled with the corresponding negative / positive electrode sheet, heating and applying a certain pressure to tightly combine the electrode sheet with the oxide electrolyte layer, and waiting to be cooled to room temperature. Due to the phase transition process of the reversible ionic liquid-based binder, the oxide electrolyte layer has strong adhesion, which improves the interface contact between the electrode sheet and the oxide electrolyte layer.

[0049] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.

[0050] Example 1

[0051] 1-Methyl-3-methylimidazolium hexafluorophosphate ionic liquid, monomer N,N-dimethylacrylamide (CAS No.: 2680-03-7), and crosslinking agent polyethylene glycol diacrylate (CAS No.: 26570-48-9) were mixed in a ratio of 6:2:2, and heated to melt at 100°C to prepare a reversible ionic liquid-based binder precursor solution; 5g LATP powder with a particle size of 0.3μm, 1g polyvinyl alcohol, and 5g reversible ionic liquid-based binder precursor solution were mixed at a speed of 1000rpm for 3h, dispersed evenly, and coated on a steel plate with a 20μm scraper, dried at 100°C, and UV-cured to obtain an oxide electrolyte layer. The electrolyte layer was placed between two stainless steel sheets, heated to 100°C, and pressed under a pressure of 30MPa to obtain a lithium-ion battery.

[0052] Example 2

[0053] 1-Methyl-3-methylimidazolium hexafluorophosphate ionic liquid, monomer N,N-dimethylacrylamide, and crosslinking agent polyethylene glycol diacrylate were mixed in a ratio of 7:1.5:1.5, and heated to melt at 100°C to prepare a reversible ionic liquid-based binder precursor solution; 5g LATP powder with a particle size of 0.3μm, 1g polyvinyl alcohol, and 5g reversible ionic liquid-based binder precursor solution were mixed at 1000rpm for 3h, dispersed evenly, and coated on a steel plate with a 20μm scraper, dried at 100°C, and UV-cured to obtain an oxide electrolyte layer. The electrolyte layer was placed between two stainless steel sheets, heated to 100°C, and pressed under a pressure of 30MPa to obtain a lithium-ion battery.

[0054] Example 3

[0055] 1-Methyl-3-methylimidazolium hexafluorophosphate ionic liquid, monomer N,N-dimethylacrylamide, and crosslinking agent polyethylene glycol diacrylate were mixed in a ratio of 8:1:1, and heated to melt at 100°C to prepare a reversible ionic liquid-based binder precursor solution; 5g LATP powder with a particle size of 0.3μm, 1g polyvinyl alcohol, and 5g reversible ionic liquid-based binder precursor solution were mixed at 1000rpm for 3h, dispersed evenly, and coated on a steel plate with a 20μm scraper, dried at 100°C, and UV-cured to obtain an oxide electrolyte layer. The electrolyte layer was placed between two stainless steel sheets, heated to 100°C, and pressed under a pressure of 30MPa to obtain a lithium-ion battery.

[0056] Example 4

[0057] 1-Methyl-3-methylimidazolium hexafluorophosphate ionic liquid, monomer N,N-dimethylacrylamide, and crosslinking agent polyethylene glycol diacrylate were mixed in a ratio of 7:1.5:1.5, and heated to melt at 100°C to prepare a reversible ionic liquid-based binder precursor solution; 3g LATP powder with a particle size of 0.3μm, 0.6g polyvinyl alcohol, and 5g reversible ionic liquid-based binder precursor solution were mixed at 1000rpm for 3h, dispersed evenly, and coated on a steel plate with a 20μm scraper, dried at 100°C, and UV-cured to obtain an oxide electrolyte layer. The electrolyte layer was placed between two stainless steel sheets, heated to 100°C, and pressed under a pressure of 30MPa to obtain a lithium-ion battery.

[0058] Example 5

[0059] 1-Methyl-3-methylimidazolium hexafluorophosphate ionic liquid, monomer N,N-dimethylacrylamide, and crosslinking agent polyethylene glycol diacrylate were mixed in a ratio of 7:1.5:1.5, and heated to melt at 100°C to prepare a reversible ionic liquid-based binder precursor solution; 1g LATP powder with a particle size of 0.3μm, 0.2g polyvinyl alcohol, and 5g reversible ionic liquid-based binder precursor solution were mixed at 1000rpm for 3h, dispersed evenly, and coated on a steel plate with a 20μm scraper, dried at 100°C, and UV-cured to obtain an oxide electrolyte layer. The electrolyte layer was placed between two stainless steel sheets, heated to 100°C, and pressed under a pressure of 30MPa to obtain a lithium-ion battery.

[0060] Example 6

[0061] 1-Methyl-3-methylimidazolium hexafluorophosphate ionic liquid, monomer N,N-dimethylacrylamide, and crosslinking agent polyethylene glycol diacrylate were mixed in a ratio of 7:1.5:1.5, and heated to melt at 100°C to prepare a reversible ionic liquid-based binder precursor solution; 3g LATP powder with a particle size of 0.1μm, 0.6g polyvinyl alcohol, and 5g reversible ionic liquid-based binder precursor solution were mixed at 1000rpm for 3h, dispersed evenly, and coated on a steel plate with a 20μm scraper, dried at 100°C, and UV-cured to obtain an oxide electrolyte layer. The electrolyte layer was placed between two stainless steel sheets, heated to 100°C, and pressed under a pressure of 30MPa to obtain a lithium-ion battery.

[0062] Comparative Example 1

[0063] 1-Methyl-3-methylimidazolium hexafluorophosphate ionic liquid, monomer N,N-dimethylacrylamide, and crosslinking agent polyethylene glycol diacrylate were mixed in a ratio of 7:1.5:1.5, and heated to melt at 100°C to prepare a reversible ionic liquid-based binder precursor solution; 3g LATP powder with a particle size of 0.3μm and 5g reversible ionic liquid-based binder precursor solution were mixed at 1000rpm for 3h, dispersed evenly, and coated on a steel plate with a 20μm scraper, dried at 100°C, and UV-cured to obtain an oxide electrolyte layer. The electrolyte layer was placed between two stainless steel sheets, heated to 100°C, and pressed under a pressure of 30MPa to obtain a lithium-ion battery.

[0064] Comparative Example 2

[0065] 3g LATP powder with a particle size of 0.3μm, 0.6g polyvinyl alcohol, 1.5g PVDF, and 5g NMP were mixed at 1000rpm for 3h, dispersed evenly, coated on a steel sheet using a 20μm scraper, and dried at 100°C. The electrolyte layer was placed between two stainless steel sheets and pressed at 30MPa to obtain a lithium-ion battery.

[0066] The thickness of the electrolyte layer obtained in the embodiment and the comparative example was tested. Meanwhile, the lithium ion battery obtained in the embodiment and the comparative example was tested for impedance using an electrochemical workstation to obtain ionic conductivity, and the peel strength was tested using a peel strength tester. The results are shown in Table 1.

[0067] Table 1 The thickness of the electrolyte layer obtained in the examples and comparative examples and the electrical properties of the lithium ion batteries

[0068] Group Thickness(μm) Ionic conductivity (mS / cm) Peel strength (N / m) Example 1 14 0.63 3.7 Example 2 14 0.72 4.2 Example 3 14 0.58 3.5 Example 4 13 0.75 4.5 Example 5 12 0.53 4.7 Example 6 12 0.48 4.3 Comparative Example 1 15 0.42 4.2 Comparative Example 2 18 0.36 0.9

[0069] It can be seen from the table that under the same ratio (Examples 1, 2, and 3), when the content of ionic liquid in the reversible ionic liquid-based binder precursor solution is about 70%, a higher peel strength can be obtained; when the proportion of the reversible ionic liquid-based binder precursor solution is higher (Examples 2, 4, and 5), the thickness of the oxide electrolyte layer can be controlled to be thinner and the peel strength is higher, that is, the bonding performance is better; when the oxide electrolyte particle size (Examples 2 and 6) is about 0.3 μm, the ionic conductivity of the oxide electrolyte layer is higher; According to Example 2 and Comparative Example 1, the addition of a dispersant can adjust the slurry viscosity and prepare a thinner oxide electrolyte layer; According to Example 2 and Comparative Example 2, a thinner oxide electrolyte layer can be prepared using a reversible ionic liquid-based binder, which can significantly improve the adhesion of the oxide electrolyte layer and improve the ionic conductivity to a certain extent.

[0070] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0071] In the embodiments of the present invention, in order to solve the problem of thick oxide electrolyte layer, a reversible ionic liquid binder is selected to prepare an ultra-thin oxide electrolyte layer that is easy to demold. At the same time, the high ionic conductivity and electrochemical stability of the ionic liquid are utilized to improve the electrochemical performance.

[0072] In the embodiment of the present invention, in order to solve the problem of poor interface contact of solid-state batteries, the added binder can make the electrolyte layer self-adhesive, the preparation process is simple, and there is no need to prepare an additional adhesive layer.

[0073] In the embodiment of the present invention, an ultra-thin oxide electrolyte layer can be prepared to improve the energy density of the battery and reduce the ion conductivity requirements of the solid electrolyte layer. The thickness of the electrolyte layer is ≤20μm, the ion conductivity is ≥0.45mS / cm, and the peel strength is ≥3.5N / m.

[0074] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A reversible ionic liquid-based binder, characterized in that: The binder is used for the solid electrolyte of lithium battery. The components of the binder include: ionic liquid, acrylamide monomer and crosslinking agent. The mass ratio of the ionic liquid, acrylamide monomer and crosslinking agent is (5-9):(0.5-2.5):(0.5-2.5).

2. The adhesive according to claim 1, characterized in that The ionic liquid is an imidazole ionic liquid, the acrylamide monomer is N,N-dimethylacrylamide, the cross-linking agent is polyethylene glycol diacrylate, and the mass ratio of the imidazole ionic liquid, the N,N-dimethylacrylamide and the polyethylene glycol diacrylate is (6-8):(1-2):(1-2).

3. The adhesive according to claim 2, characterized in that The cation of the imidazole ionic liquid includes one or more of 1-alkylimidazole, 1-alkyl-3-methylimidazole and 1-alkyl-2,3-dimethylimidazole, and the anion of the imidazole ionic liquid includes one or more of chlorine, bromine, iodine, tetrafluoroboric acid, hexafluorophosphoric acid, acetic acid, bistrifluoromethanesulfonyl imide, nitric acid, peramic acid, hydrogen sulfate, dihydrogen phosphate, trifluoromethanesulfonic acid, trifluoroacetic acid and p-toluenesulfonic acid.

4. A slurry composition, characterized in that The slurry composition is used for a solid electrolyte of a lithium battery, and the slurry composition comprises: the binder according to any one of claims 1 to 3, an oxide electrolyte powder and a dispersant.

5. The slurry composition according to claim 4, characterized in that In terms of mass fraction, the content of the binder is 50% to 80%, the content of the oxide electrolyte powder is 20% to 50%, and the content of the dispersant is 0.05% to 5%.

6. The slurry composition according to claim 5, characterized in that The oxide electrolyte powder includes: one or more of lithium lanthanum zirconium oxide, lithium aluminum titanium phosphate and lithium lanthanum titanate, and the particle size of the oxide electrolyte powder is 0.1μm to 0.3μm; the dispersant includes one or more of polyvinyl alcohol and polyvinyl acetal.

7. An ultra-thin oxide electrolyte layer, characterized in that: The electrolyte layer is formed by curing the slurry composition according to any one of claims 4 to 6, and the electrolyte layer meets at least one of the following properties: thickness ≤ 20 μm, ion conductivity ≥ 0.45 mS / cm, and peel strength ≥ 3.5 N / m.

8. A method for preparing an ultra-thin oxide electrolyte layer according to claim 7, characterized in that: The method comprises: The ionic liquid, acrylamide monomer and cross-linking agent are mixed and heated to melt to obtain a binder; The binder, the oxide electrolyte powder and the dispersant are mixed to obtain a slurry composition; The slurry composition is coated on the surface of a hard substrate, and then heated, baked and photocured to obtain a substrate with an ultra-thin oxide electrolyte layer.

9. The method according to claim 8, characterized in that The heating and baking temperature is 80° C. to 100° C., and the light curing adopts 365 nm ultraviolet rays.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the ultra-thin oxide electrolyte layer of claim 7.

Citation Information

Cited By

  • Multistage thermal response ionic crystal reversible adhesion adhesive and preparation method thereof

    CN120843026A